2016
DOI: 10.1017/s1355617716000060
|View full text |Cite
|
Sign up to set email alerts
|

Modern Methods for Interrogating the Human Connectome

Abstract: Objective Connectionist theories of brain function took hold with the seminal contributions of Norman Geschwind a half century ago. Modern neuroimaging techniques have expanded the scientific interest in the study of brain connectivity to include the intact as well as disordered brain. Method In this review, we describe the most common techniques used to measure functional and structural connectivity, including resting state functional MRI, diffusion MRI, and electroencephalography and magnetoencephalography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 171 publications
1
14
0
Order By: Relevance
“…Many techniques are currently available to study functional brain connectivity, including EEG, magnetoencephalography (MEG), functional near-infrared spectroscopy (NIRS), and task-related functional MRI Farroni et al, 2013;Omidvarnia et al, 2014) (see for review of the most commonly employed techniques (Lowe et al, 2016)); however this review will primarily address resting state functional connectivity studies. Resting state functional MRI (rs-fMRI) employs spontaneous fluctuations in blood oxygen level dependent (BOLD) signal at low frequencies (0.01-0.1 Hz) across the entire brain at a millimeters' resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Many techniques are currently available to study functional brain connectivity, including EEG, magnetoencephalography (MEG), functional near-infrared spectroscopy (NIRS), and task-related functional MRI Farroni et al, 2013;Omidvarnia et al, 2014) (see for review of the most commonly employed techniques (Lowe et al, 2016)); however this review will primarily address resting state functional connectivity studies. Resting state functional MRI (rs-fMRI) employs spontaneous fluctuations in blood oxygen level dependent (BOLD) signal at low frequencies (0.01-0.1 Hz) across the entire brain at a millimeters' resolution.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, advanced MRI techniques (functional MRI (fMRI), functional connectivity MRI and diffusion MRI imaging)) have been used to study brain function as well as structure (cf. the review [122]), though it is likely that only the interplay between structure and dynamics gives rise to function [123]. A connectivity analysis of the default mode network of the brain in a resting state found that its activity was attenuated during cognitive processing [124].…”
Section: The Brain the Heart And Beyondmentioning
confidence: 99%
“…Other correlated and anticorrelated brain networks can be identified depending on the robustness of the dataset, which increases with scan time and decreases with patient motion. 32,33 Statistical postprocessing of rs-fMRI is required to filter out noise over the temporal dataset, including low-level fluctuations related to physiological cardiac and respiratory variation. 34,35…”
Section: Blood Oxygen Level-dependent Techniquementioning
confidence: 99%